Comparison between invasive and non-invasive blood pressure in young, middle and old age. (3rd May 2016) - Liu, Bing; Li, Qiao; Qiu, Peng
Abstract: We aimed to compare simultaneous invasive and non-invasive blood pressure (IBP and NIBP) measurements in young, middle and old age using the data from the Multiparameter Intelligent Monitoring in Intensive Care II (MIMIC II) database. In total, 23, 679 blood pressure measurements were extracted from 742 patients, divided into three groups of young, middle and old age. IBP–NIBP differences in systolic/diastolic blood pressure (SBP/DBP) were 0.1 ± 16.5 mmHg/11.0 ± 12.2 mmHg in young age, –2.9 ± 19.8 mmHg/6.9 ± 17.5 mmHg in middle age and –3.2 ± 29.3 mmHg/8.5 ± 19.8 mmHg in old age. The mean and standard deviation (SD) of invasive systolic blood pressure (ISBP)–non-invasive systolic blood pressure (NISBP) differences increased from young to middle then to old age, and the SD of invasive diastolic blood pressure (IDBP)–non-invasive diastolic blood pressure (NIDBP) differences also increased with age. In young, middle and old age, the correlation coefficients were 0.86, 0.79 and 0.53, respectively, between ISBP and NISBP, and 0.78, 0.78 and 0.41 between IDBP and NIDBP. In conclusion, IBP showed good correlation with NIBP in each age category. The agreement between IBP and NIBP measurements was influenced by age category.